The use of a pesticide - foliar fertilizer mixture in mango cultivation in Malaysia. - Singh, Gurhan (1980)
Foliar applications of a mixture of an insecticide (dicrotophos) at 0.1 percent a.i., a fungicide (maneb + zinc salt) at 0.2 percent a.i. and a foliar fertilizer (Welgro standard) at 1 gm/litre was used on Harum Manis variety with a view to simultaneously controlling insects, disease and to sti,ulate flowering. Untreated trees suffered 25.8 percent, 30.9 percent and 30.3 percent damage by D.marginatus durimg the respective stages (i) before flowering (ii) during flowering and (iii) druting fruit set. The percentage incidence of minor insect pests during these three stages was marginal. Likewise disease occurrence (caused mainly by c.gloeosporoides) on foliage was minimal. However, disease (caused mainly by c.gloeosporoides)was highly damaging to floral panicles during flowering (87 percent) and during fruit set (100 percent).